Strategi Komunikasi Tanggap Karawang Dalam Upaya Peningkatan Pelayanan Infrastruktur Publik Menggunakan Instagram @Tanggap.Karawang - Aliansyah, Kiki Lucki; Nayiroh, Luluatu; Oxcygentri, Oky (CV. ITTC INDONESIA, 2024)
Tanggap Karawang is an initiative launched by the Communication and Information Office of Karawang Regency to improve public services through the use of social media, particularly Instagram. The program aims to bridge communication between the government and the community, enabling quick responses to complaints and suggestions related to infrastructure and other social issues. Through Instagram, Tanggap Karawang focuses on disseminating up-to-date information, project transparency, and community involvement in maintenance and oversight processes. This study analyzes the effectiveness of using Instagram as a communication and participation tool by evaluating the program's impact on public satisfaction and infrastructure improvement. The results show that Instagram is effective in enhancing government interaction and responsiveness to social and infrastructure issues, though challenges remain in content management and communication consistency. Recommendations for further improvement include optimizing content strategies, training social media teams, and increasing collaboration among various stakeholders